1988
DOI: 10.1200/jco.1988.6.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Short-term therapy for acute myelogenous leukemia.

Abstract: Since 1978, 187 patients (age range, 15 to 59, median 44 years) have received short-term chemotherapy as part of three sequential open studies (B-IX, X, Xb) or a randomized clinical trial (B-XI). An intended six cycles of Adriamycin (ADR) (doxorubicin; Adria Laboratories, Columbus, OH), cytarabine (ara-C), and thioguanine (TG) were administered with as short an intercycle time as possible. No further therapy was administered. Complete remission (CR) was achieved in 118 of 187 patients (63%). On univariate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…1 However, the majority relapses without any further post-remission treatment. Therefore, post-remission therapeutic strategies have been progressively intensified, [2][3][4] including high-dose chemotherapy followed by infusion of allogeneic or autologous stem cells. The role of auto-SCT in the treatment of patients with AML in first CR remains unsettled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, the majority relapses without any further post-remission treatment. Therefore, post-remission therapeutic strategies have been progressively intensified, [2][3][4] including high-dose chemotherapy followed by infusion of allogeneic or autologous stem cells. The role of auto-SCT in the treatment of patients with AML in first CR remains unsettled.…”
Section: Introductionmentioning
confidence: 99%
“…The role of auto-SCT in the treatment of patients with AML in first CR remains unsettled. Although allo-SCT is considered the most effective anti-leukemic treatment available for young patients with high-risk AML in first CR, 1,2 there is a certain degree of controversy on the best therapeutic approach for other patient populations. The results from early phase III trials have generally shown that auto-SCT results in a lower relapse rate than conventional chemotherapy that results in a modest improvement in the disease-free survival (DFS).…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of Ara-C and etoposide is shown in Table IV. (Hurd, 1987;Powles et al, 1980a;Mayer, 1987;Preisler et al, 1987a;Cassileth et al, 1987;Rohatiner et al, 1988). This is partly attributable to lack of matched sibling donors for many patients, increased drug toxicity in the elderly, and a high incidence of relapse particularly in FAB subtypes with a monocytic component (Hurd, 1987;Mayer et al, 1987;Peterson et al, 1987).…”
Section: Methodsmentioning
confidence: 99%
“…These results, however, depend upon obtaining remission, higher CR rates rendering more patients eligible for a bone marrow transplant procedure (Powles et al, 1980a). Recent clinical trials using various combinations of drugs including anthracyclines have not resulted in significantly improved remission rates, and have usually involved protracted treatment (Mayer, 1987;Preisler et al, 1987a;Cassileth et al, 1987;Capizzi et al, 1987;Rohatiner et al, 1988). Treatment-related morbidity is thus increased, with the attendant financial burdens of hospitalisation, together with continued requirement for blood product and antibiotic support. Etoposide is effective in the treatment of acute leukaemia (AL) (Gore et al, 1989;O'Dwyer et al, 1985), and preclinical trials have shown it to be synergistic when used in conjunction with Ara-C (Rivera et al, 1975).…”
mentioning
confidence: 99%
“…33 With modern chemotherapy regimens, the initial response rate is 60-65% for all patients, with a median duration of remission of 18-24 months and 20% remaining disease free for up to 12 years. 9,39 The complete response rate for identically treated patients older than 60 is < 50%.…”
Section: Discussionmentioning
confidence: 99%